Effect of variable sowing ratios and sowing rates of bitter vetch on the herbage yield of oat-bitter vetch mixed cropping - Turk, Munir; Tawaha, Abdel-Rahman (MTT, 2004)
Small grain cereals following fallow predominate the rain-fed arable land of the Mediterranean basin (Caballero 1993). Integrating winter annual legumes into crop rotations has been recommended as a means of reducing the use of nonrenewable resources (Papastylianou & Danso 1991). Caballero and Goicoechea (1986) has shown oat to be the most suitable companion crop for common vetch (Vicia sativa L.) and hairy vetch (V. villosa Roth.). The objectives of the present study were to determine whether mixtures of bitter vetch [V. ervilia (L.) Willd.] with oat would change vetch and total yield in a competitive or facilitative way related to sowing proportions based on number of seeds. Field trials were carried out at the Jordan University of Science and Technology in Northern Jordan. Ratios of the number of vetch to oat seed were 100:0; 85:15; 70:30; 65:35 and 40:60 within each mixture, sowing rates of bitter vetch were 85, 100. 115 and 130 kg ha-1. The oat was sown at 150 kg ha-l. Plants were harvested at the pod setting stage of vetch. Mixed cropping produced 90% more dry matter than the sole cropping of vetch, but 70% less than the oat sole cropping. Mixed cropping yields were not simulated by sowing ratio or sowing rate of vetch but proportions of vetch dry matter decreased linearly as the percentage of oat seed in the mixture increased. The data suggested the possibility of greatest vetch yield with oat proportions below 20%. If high herbage yield is the objective, the oat sole crop will be selected. Crude protein content should not be a criterion to define the best sowing rate of oat-vetch mixture. High forage quality of the mixed cropping would require a very low sowing proportion of oat to increase vetch contribution to forage yield. Caballero, R. & Goicoechea, E. L. 1986. In: Barba, F. M. & Abreu, J. M. (eds.). Grasslands facing the energy crisis. Proceeding of the 11th General meeting of the European Grassland Federation, pp.379-384; Caballero, R. 1993. Journal of Sustainable Agriculture, 3: 133-154; Papastylianou, I & Danso, D. K. 1991. Soil, Biology and Biochemistry 23:447-452.
Keywords: Ka; Sole cropping; mixed cropping; Vicia; Avena